The differences between mangosteen peel extract irrigant and NaOCl 2.5% on root canal cleanliness - Cornelia Melinda Adi Santoso; Karlina Samadi; Eric Priyo Prasetyo; Dian Agustin Wahjuningrum (Conservative Dentistry Journal, 2020)
Background: Preparation, one of the stages in root canal treatment, always producesdebrisas aresultof instrumentation onroot canalwalls. Debrisconsistsoforganicand inorganicmaterials. Irrigation need to be performed in every preparation so that debrisandmicroorganisms can be removed from root canal wallsthrough flushingmechanism. NaOCl 2.5% is the most popular irrigant used in root canal treatment. However, NaOCl2.5% onlyworks onorganic tissue. Mangosteenpeel extractcontainsvariousactive compounds, such as saponin. Saponin acts assurfactantso as tolower thesurface tension and remove debris from the root canalwalls. Purpose: to compare the cleanliness of root canal walls following irrigation with NaOCl 2.5% and mangosteen peel extract. Method: Eighteen mandible premolar extracted for orthodontics necessity were used in this study. The teeth were divided into three groups, in which each group consists of six teeth. All of them were instrumented with ProTaper for Hand Use and irrigated. Group 1 used aquadest as irrigant, group 2 used NaOCl 2,5%, and group 3 used mangosteen peel extract 400 ug/ml. The roots were split longitudinally into halves and in 1/3 of apex. The surface of the canal walls were examined using scanning electron microscope. Photomicrographs were scored by three independent observers and statistically tested. Result: There were significant differences between three groups (p<0.05). Group 3, irrigated with mangosteen peel extract 400 ug/ml, had the smallest median score that was 1. Conclusion: Mangosteen peel extract is moreeffective thanNaOCl 2.5% incleaningroot canalwall from debris.